ENTREPRENEURIAL MOTIVATION IN BUSINESS EDUCATION STUDENT GRADUATES IN PHENOMENOLOGICAL STUDY - Pratesa, Dimas Putri Mega; Anfi, Dieva Zahrohtu; Rahma, Adelia; Yoga, Sumarsetio (PUSAT KEWIRAUSAHAAN UNIVERSITAS BALIKPAPAN, 2023)
Universities as centers for the development of science encourage students to carry out entrepreneurial activities. As happened in the Business Education Study Program, State University of Malang, where Bachelor of Education graduates not only work as educators or employees, but also as entrepreneurs. Becoming an entrepreneur, especially for Business Education graduates, is influenced by various motivations. Therefore, this research aims to explore in depth the motivational phenomena that encourage Business Education graduates to become entrepreneurs. The subjects in this research were 5 Business Education graduates from the State University of Malang. Research was carried out in depth using interviews, observation, documentation and audiovisual. Based on research, two main keys to motivation were found, namely internal stimulus and external stimulus